FREEDOM FOR CHICKENS – THE INFLUENCE OF THE SILVOPASTORAL SYSTEM ON POULTRY BEHAVIOR - Camarero, Nina Publio; Righi, Ciro Abbud; Sabadin, Eloá Ruffini; Silva, Iran José Oliveira da; Menten, José Fernando Machado; do Couto, Hilton Thadeu Zarate (REVISTA DE AGRICULTURA, 2023)
Egg is a worldwide appreciated cooking ingredient. To meet the consumption demand in a fast growing human population, the process of raising chickens developed over the years to an industrial scale in which birds are kept in stacked cages and unable to develop their behavior. The current demand for animal products raised in more ethical systems places conventional poultry farming as one of the main targets of criticism. On the other hand, it is possible to think about raising these birds in agroforestry systems bringing these birds closer to their habitat of origin. This would allow improvements in birds life and produce food of greater quality and value. In this work, a Poultry Silvopastoral System (SSP) was developed. The systems of raising chickens in agroforestry environment or confined in barns (cage-free) were comparatively evaluated in terms of birds’ behavior in response to the contrasting environment. In this initial trial we observed that birds in SSP spent about 30% of the time scratching, while those in confined space only 13% of the time. In addition, a higher occurrence of behaviors related to the limitations of the environment was observed for hens raised in confinement, such as “non-aggressive pecking”, “exploring feathers” and “perching” indicating tedious. The similarities between the agroforestry environment and the chicken’s original habitat stimulated a greater occurrence of natural behavior, favoring their well-being. More detailed and long-term researches are need in order to integrate this important animal into especially developed SSPs.